Overcome the stigma to dementia, a challenge to the Cuban society - Rodolfo Isidro Bosch Bayard; Juan de Jesús Llibre Rodríguez; Tania Zayas Llerena; Elaine Hernández Ulloa (Universidad de Ciencias Médicas de La Habana, 2017)
Introduction: Worldwide Alzheimer Disease Organization in the year 2012 carried out a campaign to overcome the stigma to dementia. The stigma constitutes the biggest obstacle to identify health's problems of, to find its solutions and to use in a more efficient way the health's services. Objective: To show it repercussion of the stigma to the patient with dementia, the family and the society. Material and Methods: It was carried out a search of the published literature in the period comprised from July 2010 until March 2016. The information was obtained through Infomed information network, we used the following databases, Pubmed, Ebsco, Medline, Sciencedirect, Clinicalkey and Scielo. The data obtained was analyzed and commented. Development: The stigma interferes in that people with dementia have a successful social life, obtain employments and to have the possibility to live near other people. It has a big relationship with the age and the loss of the mental functions. The areas of bigger impact of the stigma are: the labor sphere, vehicles driving, the possibility to give consent for the medical procedure that have influence in a premature loss of dignity and autonomy. Conclusions: To overcome the stigma that today exists to dementia it is necessary to offer a bigger acceptance and support to the patients and family, to increase care's quality for people with cognitive deterioration, to educate the population, to create a favorable environment, to create social network of support and to call the for participation of all the sectors of the society. Keywords: social stigma, dementia, social discrimination, health plan, family, society, Cuba.